Filmes de nanocompósitos de polímero condutor, nanopartículas de argila e nanopartículas de ouro para aplicação em sensores ambientais - Barros, Anerise de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work, nanocoposites of polyaniline emeraldine salt (PAni-ES), organophilic montmorillonite clay (MMTO) and sodium (Na+-MMT) and gold nanoparticles (AuNPs) were obtained through the techniques of Langmuir-Blodgett (LB) and Layer-by-Layer (LbL). The materials were deposited on various solid substrates and characterized by spectroscopic and microscopic methods, in order to ascertain the interaction and synergy between the materials involved. Satisfactory results were obtained by the methods of characterization of the films by ultraviolet visible (UV-vis), Fourrier transform Infrared spectroscopy (FTIR), Raman spectroscopy and atomic force microscopy (AFM), showing the efficiency in the process of obtaining nanocomposites through the LbL and LB techniques. In general, the results demonstrated influences the properties of the clays in the PAni-ES altering the condutivity thereof. Although the clays decreased the conductive properties of PAni-ES, but still is a good feature observed the presence of clays decreased the conductive properties of PAni-ES, but still is a good feature observed the presence of clay in the nanocomposite films to maintain their properties during electrochemical processes. Morphological analysis by AFM shows interesting characteristics for the films of polymer-clay nanocomposites, with less rough and consequently thinner films. The nanostructure films were evaluated how sensing unit from the electrochemical methods, by cyclic voltammetry (CV) and square wave anodic stripping voltammetry (SWASV). Aiming the application for the environmental area to detect metal ions of copper, lead and cadmium (cu2+, Pb2+ e Cd2+). The insertion of tiolateds gold nanoparticles (AuNPs) favors the increase in conductivity of the films, thus promoting the catalytic activity of the sensors. Consequently increase the sensibility and lower limit of detection when compare to the films absent of gold nanoparticles

Neste trabalho nanocompósitos de polianilina sal esmeraldina (PAni-ES), argilas montmorilonitas organofilica (MMTO) e sódica (MMT-Na+) e nanopartículas de ouro (AuNPs) foram obtidos através das técnicas de fabricação de filmes nanoestruturados, Langmuir-Blodgett (LB) e Layer-by-Layer (LbL). Os materiais foram depositados em diferentes substratos solidos, e caracterizados através de métodos espectroscópicos e microscópicos, a fim de verificar as interações entre os materiais envolvidos. Resultados obtidos através das caracterizações por ultravioleta visível (UV-vis). Infravermelho com transformada de Fourrier (FTIR), Raman e microscopia de força atômica (AFM), indicaram a eficiência no processo de obtenção de nanocompósitos através das técnicas LB e LbL. Mais especificamente, os resultados espectroscópicos indicaram que as interações das argilas e/ou AuNPsMES, influenciam principalmente nas propriedades condutoras da PAni-ES. Por outro lado, rseultados de difratometria de raio X (XRD) indicaram a formação de nanocompósitos através da intercalação dos materiais nos espaços interlamentares da argila. Análises morfológicas por AFM revelaram que a sinergia entre os materiais favorece a obtenção de filmes menos rugosos e homogêneos. Os filmes nanoestruturados em diferentes arquiteturas foram avaliados como unidades sensoriais, através de métodos eletroquímicos por voltametria cíclica (VC) e voltametria de onda quadrada por redissolução anódica (SWASV). Visando à aplicação para área ambiental na detecção de íons metálicos de cobre, chumbo e cádmio (Cu2+, Pb2+ e Cd2+). A inserção das nanopartículas de ouro tioladas (AuNPs.MES) favoreceram em um aumento na condutividade dos filmes, promovendo melhor atividade catalítica para os sensores. Consequentemente, aumentando a sensibilidade e atingindo menores valores de limite detecção (LD), quando compacto aos filmes ausentes de nanopartículas de ouro
Keywords: Nanopartículas; Ions metalicos; Detectores infravermelhos; Filmes finos multifolhados; Nanoparticles